2011
DOI: 10.1016/j.ejcts.2010.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Single-center 50 years’ experience with surgical management of tetralogy of Fallot☆

Abstract: Surgical treatment of the tetralogy of Fallot and related congenital cardiac malformations has good long-term prognosis. In this cohort of patients, more than one-third required additional procedures later on, and, in some cases, as many as four additional surgeries. Palliative procedures followed by repair do not influence survival or reoperation-free survival. There are no differences between transatrial versus transventricular repair on survival or re-repair. Any transannular incision increases the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 12 publications
5
56
1
Order By: Relevance
“…Palliative procedures followed by repair do not influence survival or reoperation-free survival, as previously shown by Lindberg et al [24]. The implantation of an RV-PA tube significantly and independently increases the risk of RVOT obstruction and reoperation.…”
Section: Discussionsupporting
confidence: 59%
“…Palliative procedures followed by repair do not influence survival or reoperation-free survival, as previously shown by Lindberg et al [24]. The implantation of an RV-PA tube significantly and independently increases the risk of RVOT obstruction and reoperation.…”
Section: Discussionsupporting
confidence: 59%
“…centers in developed countries perform successful total correction with no early mortality, [5][6][7] while in developing countries mortality rates are as high as 6.9-15.3%. 8,9 In our study, the early mortality rate after total repair of TOF was 7.3%.…”
Section: Discussionmentioning
confidence: 99%
“…13 As studies have demonstrated significant morbidity, increased mortality and late re-operation rates for infants who undergo repair before 3-6 months of age, shunting is still preferred by many for symptomatic neonates and younger infants. 6,12,14,15 In 13 of our patients (10%), surgery was performed before 1 year of age and, the youngest patient was being 4.5 months old. We didn't find the age and weight at the time of surgery to be strongly correlated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The major benefits of early repair are avoidance of RV hypertrophy and its consequences, elimination of cyanosis, and the preservation of pulmonary angiogenesis and alveologenesis [12,22]. A number of pediatric cardiac programs strongly favor an aggressive AP strategy [1,16,19,21,23,25], which may prevent the deleterious effects of pulmonary insufficiency and its consequences [2,5,9,17]. Because patients with neonatal early repair are deemed to have a higher risk of TAP [6], some would argue that overly aggressive AP strategy can pose a dilemma for surgeons who also advocate early primary repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of controversies have remained unsettled, including the optimal right ventricular outflow tract (RVOT) reconstruction method for each patient with different disease severity. Given that a large number of patients with repaired ToF may require late postoperative pulmonary valve implantation (PVI) to alleviate the risk of right ventricular dilatation, ventricular arrhythmia, and sudden death [4,9,17], it is important to minimize the risk of later postoperative pulmonary regurgitation at the time of initial repair. RVOT reconstruction with pulmonary annulus preservation (AP) is generally believed to be superior to transannular patching (TAP) for the prevention of late-onset pulmonary insufficiency and RV dilatation [2].…”
Section: Introductionmentioning
confidence: 99%